Analysis of conditions for synthesis of CdS:Mn nanoparticles - Kovalchuk, A.O.; Rudko, G.Yu.; Fediv, V.I.; Gule, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The detailed analysis of the synthesis of CdS:Mn nanoparticles in polyvinyl alcohol polymeric matrix is presented and the ranges of optimal growth parameters are determined. The estimated values of parameters were used to produce solutions of CdS:Mn nanoparticles and corresponding solid composites. The sizes of nanoparticles and structure of composite films were characterized by electron microscopy methods, optical properties were probed using photoluminescence methods.